Preparation method of lanthanum-calcium doped permanent magnet ferrite pre-sintering material

CN122916646APending Publication Date: 2026-10-16SHANGHAI BAOSTEEL MAGNETICS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611394937.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0008]为了解决上述问题,针对现有永磁铁氧体预烧料掺杂改性普遍依赖镧-钴-钙三元体系、钴原料成本高昂,以及传统铁锶单一配方成本高、性能稳定性一般、传统泵送工艺工况不稳定、产品批次一致性差的技术痛点,本发明公开了一种镧钙掺杂永磁铁氧体预烧料制备方法,首次采用单独镧钙二元掺杂替代部分碳酸锶,在不引入钴元素的前提下保证预烧料磁性能与传统工艺相当,同时降低原料成本;同时采用螺旋绞龙密闭稳流输料替代传统软管泵送,稳定窑炉工况、提升产品一致性,适配低成本、高品质、规模化工业化连续生产

Benefits of technology

[0018] By adopting the above technical solution, the dehydrated slurry is directly transported to the kiln through a spiral auger, and the pre-firing temperature and holding time are matched precisely to ensure that the solid phase reaction in the kiln is fully and uniformly carried out, effectively optimizing the morphology and phase purity of ferrite grains. After cooling, high-performance and high-stability lanthanum-calcium doped permanent magnet ferrite pre-fired material is obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention relates to the field of permanent magnet ferrite material preparation technology, and discloses a method for preparing lanthanum-calcium doped permanent magnet ferrite pre-sintered material. The method uses Fe2O3, SrCO3, La2O3, CaCO3, and trace amounts of SiO2 as raw materials, employing a single lanthanum-calcium binary composite doping system to replace part of the strontium carbonate. The raw material mass percentages are: Fe2O3 85.2%–87.2%, SrCO3 11.3%–12.3%, La2O3 1.4%–1.6%, CaCO3 0.4%–0.6%, and SiO2 0–0.2%. The material is wet-milled for 1.8–2.2 hours, centrifuged to control the slurry moisture content to 33%–37%, and then conveyed into a kiln via a closed spiral auger. The pre-sintered material is then obtained by constant-temperature pre-firing at 1260℃–1300℃. This invention achieves magnetic properties comparable to traditional processes by using lanthanum-calcium binary doping without the use of cobalt, while reducing raw material costs. Combined with centrifugal dehydration and auger steady-flow feeding processes, it improves feeding stability, enhances batch consistency, and is suitable for large-scale industrial continuous production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of permanent magnet ferrite material preparation technology, specifically a method for preparing lanthanum-calcium doped permanent magnet ferrite pre-sintered material. Background Technology

[0002] Permanent magnet ferrites are widely used in motors, electronic devices, home appliances, and the automotive industry due to their advantages such as high cost-effectiveness, stable magnetic properties, good corrosion resistance, and mature technology. Pre-sintered materials are the core raw materials for preparing high-performance permanent magnet ferrites; the grain morphology, phase purity, and compositional uniformity of the pre-sintered materials directly determine the magnetic properties and stability of the final ferrite product.

[0003] In the field of permanent magnet ferrite doping modification technology, the industry commonly uses a lanthanum-cobalt-calcium (La-Co-Ca) ternary composite doping system. This system leverages the anisotropy of cobalt to improve magnetic properties such as coercivity. However, cobalt raw materials (such as Co2O3 and CoCO3) are expensive, and introducing cobalt into the formulation significantly increases the cost of pre-sintered materials. Currently, there are virtually no publicly available reports on using a lanthanum-calcium (La-Ca) binary system alone for permanent magnet ferrite doping modification. This suggests that existing technology generally considers cobalt as essential for achieving the desired doping effect. Whether a single lanthanum-calcium binary doping system can achieve equivalent magnetic properties without using cobalt is a matter of technical bias for those skilled in the art.

[0004] In addition, the current traditional wet process for preparing ferrite pre-sintered materials for permanent magnets has the following technical and cost defects: First, traditional conventional ferrite formulations mostly use a single formulation system of iron and strontium with additives. The market price of strontium carbonate is high and the amount used is large, resulting in high production costs of pre-sintered materials and a need to improve the cost-effectiveness of the products. Second, the single formulation of iron and strontium with additives has limited effect on ferrite lattice refinement and defect repair. The uniformity of the grains in the prepared pre-sintered materials is generally poor, and there are defects in the microstructure, and the stability of magnetic properties needs to be improved. Third, the traditional wet process in the industry generally uses a hose pump to deliver the slurry into the kiln. The pumping process has large pressure fluctuations, the slurry is prone to solid-liquid separation, and the instantaneous feed rate is uneven. This causes frequent fluctuations in the kiln heat load and uneven heating of the material, which easily leads to quality problems such as uneven grain size, local agglomeration, under-burning or over-burning of the pre-sintered materials. The batch consistency of the products is poor, which restricts the kiln capacity and the improvement of the yield of finished products.

[0005] In summary, current technologies generally rely on the lanthanum-cobalt-calcium ternary system for doping modification, and cobalt raw materials are expensive. There is currently no technical solution for separate lanthanum-calcium binary doping modification. Furthermore, traditional flexible hose pump feeding processes suffer from large fluctuations in operating conditions and poor product consistency. The industry lacks an integrated preparation process that achieves low cost, high performance, and high stability without using cobalt, and there is no technical solution that couples a separate lanthanum-calcium doping formulation, centrifugal dehydration, and auger constant-flow feeding.

[0006] Document CN 106608725 A discloses a Ca-La-Co-Fe-FO permanent magnet ferrite material and its preparation method. The method involves using calcium carbonate, lanthanum oxide, iron oxide, cobalt oxide, and calcium fluoride as raw materials, and mixing them according to their chemical formulas. Simultaneously, 0.45-0.5% calcium gluconate and 0.45-0.5% nano-Si are added to obtain a primary batch. The prepared material is pre-calcined at 1220℃-1310℃ in an oxygen-rich atmosphere for 2.5-3.0 hours, then naturally cooled, pulverized using a vibratory mill, and passed through a 100-120 mesh sieve to obtain the pulverized pre-calcined material. A certain amount of the pulverized pre-calcined material is weighed for a secondary batching. One or more of SrCO3, BaCO3, CaCO3, BiO, and CuO are added, along with 3-3.5% NH4+ for pH adjustment and 5-5% NH4+. 0.5% grape calcium carbonate is used to obtain secondary batching; the secondary batching material is fed into a planetary ball mill and ball-milled to an average particle size of about 0.66 micrometers; the slurry is concentrated to a weight content of 17-37% deionized water; the slurry is pressed into triangular blocks and simultaneously subjected to magnetic field orientation at a pressing pressure of 15-30 MPa and an orientation magnetic field of 13000-15000 Oe; 6) the resulting blocks are sintered at a sintering temperature of 1120-1350℃ and held at this temperature for 3.5-5 hours in an oxygen-rich atmosphere. This method is prone to stratification during pumping, which can cause segregation of dopant elements and large batch performance fluctuations.

[0007] Therefore, a new technical solution is needed to solve the above-mentioned technical problems. Summary of the Invention

[0008] To address the aforementioned issues, and considering the technical pain points of existing permanent magnet ferrite pre-sintering materials, which generally rely on the lanthanum-cobalt-calcium ternary system for doping and modification, resulting in high cobalt raw material costs, as well as the high cost, mediocre performance stability, unstable operating conditions, and poor batch consistency of traditional iron-strontium single-component formulations, this invention discloses a method for preparing lanthanum-calcium doped permanent magnet ferrite pre-sintering materials. This method, for the first time, uses a single lanthanum-calcium binary doping process to replace part of the strontium carbonate, ensuring that the magnetic properties of the pre-sintering material are comparable to those of traditional processes without introducing cobalt, while simultaneously reducing raw material costs. Furthermore, it employs a spiral auger closed-loop stable flow conveying system instead of traditional flexible hose pumping, stabilizing kiln conditions, improving product consistency, and adapting to low-cost, high-quality, large-scale industrial continuous production.

[0009] The technical solution of this invention is: a method for preparing lanthanum-calcium doped permanent magnet ferrite pre-sintered material, comprising the following steps: Step 1, Precise ingredient proportioning: Weigh each raw material component according to its mass percentage; Step 2, wet ball milling: The prepared raw materials and water are put into a wet ball mill, and the solid-liquid mass ratio is controlled to perform constant temperature wet ball milling to obtain a mixed slurry with uniform particle dispersion and composition. Step 3, centrifugal dewatering: The ball-milled mixture is fed into a centrifuge for high-speed centrifugal dewatering to control the moisture content of the dewatered slurry; Step 4, pre-firing by spiral auger: The dehydrated slurry is conveyed to the kiln in a closed manner through a spiral auger, pre-firing at a constant temperature, and then cooled, crushed and coarsely ground to obtain lanthanum-calcium doped permanent magnet ferrite pre-firing powder.

[0010] Preferably, the raw material components are in the following mass percentages: Fe2O3 85.2%–87.2%, SrCO3 11.3%–12.3%, La2O3 1.4%–1.6%, CaCO3 0.4%–0.6%, and SiO2 0–0.2%.

[0011] Preferably, the SrCO3 in step 1 is a binary composite doping system of La2O3 and CaCO3, which achieves ferrite lattice modification through the synergistic effect of lanthanum and calcium ions.

[0012] By adopting the above technical solution, using lanthanum and calcium binary components for composite doping modification, and replacing part of the strontium carbonate in equal amounts, compared with the traditional cobalt-containing doping formula, the high cost of cobalt raw materials is avoided from the source. At the same time, it accurately adapts to the modification requirements of M-type hexagonal ferrite lattice, ensuring that the magnetic properties of the material are on par with those of traditional processes.

[0013] Preferably, in step 2, the solid-liquid mass ratio is controlled to be 1:1.3 to 1:1.4, and the constant temperature wet ball milling is carried out for 1.8 to 2.2 hours. After the wet ball milling is completed, the median particle size D50 of the slurry is controlled to be 1.0 to 1.5 μm.

[0014] By adopting the above technical solution, the mixed raw materials and water are fed into a wet ball mill, and the optimal solid-liquid ratio and ball milling time are matched to achieve full refinement of raw material particles and uniform dispersion of components. This effectively avoids the problems of particle agglomeration and energy waste caused by excessive ball milling, ensures the uniformity of material mixing, and lays a good material foundation for subsequent solid-phase pre-calcination reaction.

[0015] Preferably, the moisture content of the slurry after dewatering in step 3 is 33% to 37%, and the centrifuge is a horizontal screw centrifuge.

[0016] By adopting the above technical solution, the slurry after ball milling is dehydrated by high-speed centrifugation, and the moisture content of the slurry is controlled within the range of 33% to 37%. At this moisture content, the material has moderate fluidity and no agglomeration, making it suitable for closed spiral conveying equipment. It can achieve continuous, uniform, and stable feeding without stratification, eliminating the need for pretreatment processes such as drying, crushing, and granulation, and avoiding the defects of solid-liquid stratification and flow fluctuation in traditional hose pumping.

[0017] Preferably, in step 4, the kiln pre-firing and heat preservation time is 3-4 hours, the constant temperature pre-firing temperature is 1260℃-1300℃, and the kiln is a rotary kiln.

[0018] By adopting the above technical solution, the dehydrated slurry is directly transported to the kiln through a spiral auger, and the pre-firing temperature and holding time are matched precisely to ensure that the solid phase reaction in the kiln is fully and uniformly carried out, effectively optimizing the morphology and phase purity of ferrite grains. After cooling, high-performance and high-stability lanthanum-calcium doped permanent magnet ferrite pre-fired material is obtained.

[0019] The advantages of this invention are as follows: 1. This invention features an innovative formulation, using a single lanthanum-calcium binary doping system to replace the cobalt-containing system for the first time, achieving cost reduction without compromising performance. Existing permanent magnet ferrite doping modification technologies generally use a lanthanum-cobalt-calcium ternary composite doping system, relying on cobalt to enhance magnetic properties. The high price of cobalt raw materials leads to high production costs. This invention breaks through the technical bias in this field and uses a single lanthanum-calcium binary composite doping system for the first time. Through the synergistic effect of lanthanum ions occupying strontium sites and calcium ions participating in lattice regulation, the M-type hexagonal ferrite lattice structure is optimized, refining the grains, regulating the microstructure, and reducing lattice defects. Without introducing any cobalt, the magnetic properties of the prepared pre-sintered material are basically on par with those of traditional cobalt-containing doped systems and pure strontium-free doped systems. At the same time, it significantly reduces the overall cost of raw materials and significantly improves the market cost-effectiveness of the product.

[0020] 2. This invention features a technological innovation: a closed-loop, stable-flow spiral auger conveying system replaces traditional hose pumping, stabilizing operating conditions and improving product consistency. Traditional hose pumping of slurry into the kiln suffers from inherent defects such as unstable pressure, solid-liquid stratification, and uneven feeding, easily leading to kiln temperature fluctuations and uneven material heating, resulting in inconsistent pre-fired material quality. This invention, coupled with a precise centrifugal dehydration process, employs a closed-loop, continuous spiral auger conveying of wet materials with low to medium moisture content, achieving constant flow, stable pressure, and continuous feeding without stratification. The kiln's heat load is stable, material heating and water vaporization are uniform, and solid-phase reactions are fully and consistently carried out, effectively improving the quality drawbacks of traditional pumping processes and significantly enhancing product batch stability and kiln's effective production capacity.

[0021] 3. This invention achieves integrated and stable preparation through the coupling and synergy of the formulation, dehydration, and feeding processes. This invention is not a simple superposition of a single lanthanum-calcium doping formulation and a spiral auger feeding process, but rather a synergistic interaction among the three: In a single lanthanum-calcium doping formulation system, the lanthanum and calcium components have low content and significant density differences. If traditional flexible hose pumps are still used for feeding, solid-liquid stratification during pumping will lead to segregation of the lanthanum and calcium doping components, uneven element distribution, and batch performance fluctuations. This invention precisely controls the slurry moisture content to 33%–37% through centrifugal dehydration, bringing the material to a plastic state suitable for spiral auger conveying. This avoids leakage and backflow caused by excessive moisture content, as well as blockage and uneven conveying caused by excessively low moisture content. Based on this, a closed spiral auger conveying system ensures that the lanthanum-calcium doping components enter the kiln uniformly and stably, achieving batch consistency in doping modification effects. The coupling and synergy of these three processes jointly achieve the technical effects of cost reduction, quality stabilization, and efficiency improvement.

[0022] 4. The parameters of this invention are precisely controllable, resulting in stable product performance and a high yield rate. This invention precisely limits the entire process, including raw material ratio, ball milling parameters, dehydration moisture content, pre-calcination temperature, and holding time, achieving standardized and controllable production. The pre-calcined material prepared has a single main phase, low impurity phase content, uniform and dense grains, and low porosity. The core indicators of the permanent magnet ferrite prepared by subsequent processing are stable, with excellent batch consistency and significantly improved product yield. It can reliably meet the needs of large-scale production of medium-to-high-end permanent magnet ferrite products. Detailed Implementation

[0023] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the solutions in the embodiments of the present invention. Example 1

[0024] A method for preparing lanthanum-calcium doped permanent magnet ferrite pre-sintered material includes the following steps: Step 1: Raw material ratio (mass percentage): Fe2O3 86.2%, SrCO3 11.8%, La2O3 1.5%, CaCO3 0.5%, SiO2 0%; Step 2, wet ball milling: After mixing the raw materials, water is added at a solid-liquid mass ratio of 1:1.35. Wet milling is carried out for 2.0 hours to obtain a uniform slurry with a median particle size D50 of 1.2 μm. Step 3, centrifugal dewatering: After centrifugation using a horizontal screw centrifuge, the moisture content of the slurry is controlled at 35%. Step 4, pre-calcination treatment: The dehydrated wet material is directly fed into the rotary kiln through a closed spiral conveyor and pre-calcined at 1300℃ for 3.0h. After cooling, crushing and coarse grinding, the pre-calcined material is obtained. Example 2

[0025] A method for preparing lanthanum-calcium doped permanent magnet ferrite pre-sintered material includes the following steps: Step 1, Raw material ratio (mass percentage): Fe2O3 86.2%, SrCO3 11.5%, La2O3 1.6%, CaCO3 0.6%, SiO2 0.1%; Step 2, wet ball milling: After mixing the raw materials, add deionized water at a solid-liquid mass ratio of 1:1.3 and wet mill for 1.8 hours to obtain a uniform slurry with a median particle size D50 of 1.4 μm. Step 3, centrifugal dewatering: After centrifugation using a horizontal screw centrifuge, the moisture content of the slurry is controlled at 33%. Step 4, pre-calcination treatment: The dehydrated wet material is directly fed into the rotary kiln through a closed spiral conveyor and pre-calcined at 1280℃ for 3.0h. After cooling, crushing and coarse grinding, the pre-calcined material is obtained. Example 3

[0026] A method for preparing lanthanum-calcium doped permanent magnet ferrite pre-sintered material includes the following steps: Step 1, Raw material ratio (mass percentage): Fe2O3 85.2%, SrCO3 12.3%, La2O3 1.4%, CaCO3 0.4%, SiO2 0.2%; Step 2, wet ball milling: After mixing the raw materials, deionized water is added at a solid-liquid mass ratio of 1:1.4. Wet milling is carried out for 2.2 hours to obtain a uniform slurry with a median particle size D50 of 1.1 μm. Step 3, centrifugal dewatering: After centrifugation using a horizontal screw centrifuge, the moisture content of the slurry is controlled at 37%. Step 4, pre-calcination treatment: The dehydrated wet material is directly fed into the rotary kiln through a closed spiral conveyor and pre-calcined at 1260℃ for 4.0h. After cooling, crushing and coarse grinding, the pre-calcined material is obtained.

[0027] Comparative example (traditional undoped wet process) Using a traditional undoped formula (Fe2O3 86.2%, SrCO3 13.7%, SiO2 0.1%), the slurry was pumped into the kiln using a hose pump, and the remaining process conditions were consistent with those in Example 1 of this invention, thus obtaining a pre-fired sample using the traditional process.

[0028] Performance vs. Cost Comparison The pre-sintered materials prepared in Examples 1-3 of this invention were compared with comparative samples from traditional undoped, hose-pumped processes. After undergoing the same subsequent fine grinding, molding, and sintering processes to produce sintered magnets, their magnetic properties were tested. Simultaneously, the overall production cost was calculated, and the quantitative comparison results are as follows: Core Magnetic Properties: The magnetic performance of the finished magnets based on the lanthanum-calcium doped system of this invention is basically consistent with that of products produced using traditional undoped processes, consistently meeting the standards for mid-to-high-end permanent magnet ferrites. This truly achieves the goal of not reducing performance while lowering costs due to the absence of cobalt. Specific test data are shown in the table below.

[0029]

[0030] Comprehensive economic benefits: This invention replaces part of the strontium carbonate with a single lanthanum-calcium binary component and completely eliminates the use of cobalt raw materials, reducing raw material procurement costs from the source. Combined with precise dehydration and a spiral auger for stable flow feeding, it effectively reduces production energy consumption, minimizes product rework losses, and increases equipment capacity. Calculations show that the overall production cost is reduced by 5%–10% compared to traditional processes, and production energy consumption is reduced by more than 5%, demonstrating significant industrial economic advantages.

[0031] This invention, through a coupled design of formula optimization and process innovation, effectively improves the industry pain points of high cost, high energy consumption and poor product stability of traditional wet process without using cobalt and while ensuring the excellent performance of permanent magnet ferrite pre-sintered material. The process is simple, highly controllable and suitable for large-scale industrial continuous production.

[0032] The above are merely preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the inventive concept and principles of the present invention should be covered within the scope of protection of the present invention. The equipment, conventional operating parameters, and supporting processes not specifically defined in the present invention are all technical means that can be conventionally selected and implemented by those skilled in the art, and need not be elaborated upon.

Claims

1. A method for preparing lanthanum-calcium doped permanent magnet ferrite pre-sintered material, characterized in that, Includes the following steps: Step 1, Precise ingredient proportioning: Weigh each raw material component according to its mass percentage; Step 2, wet ball milling: The prepared raw materials and water are put into a wet ball mill, and the solid-liquid mass ratio is controlled to perform constant temperature wet ball milling to obtain a mixed slurry with uniform particle dispersion and composition. Step 3, centrifugal dewatering: The ball-milled mixture is fed into a centrifuge for high-speed centrifugal dewatering to control the moisture content of the dewatered slurry; Step 4, pre-firing by spiral auger: The dehydrated slurry is conveyed to the kiln in a closed manner through a spiral auger, pre-firing at a constant temperature, and then cooled, crushed and coarsely ground to obtain lanthanum-calcium doped permanent magnet ferrite pre-firing powder.

2. The method for preparing lanthanum-calcium doped permanent magnet ferrite pre-sintering material according to claim 1, characterized in that: The raw material components are as follows by mass percentage: Fe2O3 85.2%–87.2%, SrCO3 11.3%–12.3%, La2O3 1.4%–1.6%, CaCO3 0.4%–0.6%, and SiO2 0–0.2%.

3. The method for preparing lanthanum-calcium doped permanent magnet ferrite pre-sintering material according to claim 1, characterized in that: The SrCO3 in step 1 may be a binary composite doping system of La2O3 and CaCO3, which achieves ferrite lattice modification through the synergistic effect of lanthanum and calcium ions.

4. The method for preparing lanthanum-calcium doped permanent magnet ferrite pre-sintering material according to claim 1, characterized in that: In step 2, the solid-liquid mass ratio is controlled at 1:1.3 to 1:1.4, and the wet ball milling is carried out at a constant temperature for 1.8 to 2.2 hours. After the wet ball milling is completed, the median particle size D50 of the slurry is controlled at 1.0 to 1.5 μm.

5. The method for preparing lanthanum-calcium doped permanent magnet ferrite pre-sintering material according to claim 1, characterized in that: In step 3, the moisture content of the slurry after dewatering is 33% to 37%, and the centrifuge is a horizontal screw centrifuge.

6. The method for preparing lanthanum-calcium doped permanent magnet ferrite pre-sintering material according to claim 1, characterized in that: In step 4, the kiln pre-firing and heat preservation time is 3-4 hours, and the constant temperature pre-firing temperature is 1260℃-1300℃. The kiln is a rotary kiln.

Citation Information

Patent Citations

  • Ca-La-Co-Fe-F-O permanent magnetic ferrite material and preparation method thereof

    CN106608725A